Antibody-based therapy in colorectal cancer. (May 2013) - Noguchi, Takuro; Ritter, Gerd; Nishikawa, Hiroyoshi
Treatment in patients with nonresectable and resectable colorectal cancer at the advanced stage is challenging, therefore intensive strategies such as chemotherapy, signaling inhibitors and monoclonal antibodies (mAbs) to control the disease are required. mAbs are particularly promising tools owing to their target specificities and strong antitumor activities through multiple mechanisms, as shown by rituximab in B-cell non-Hodgkin's lymphoma and trastuzumab in breast cancer. Three mAbs (cetuximab, bevacizumab and panitumumab) have been approved for the treatment of colorectal cancer in the USA and many other mAbs are being tested in clinical trials. The potential of antibody therapy is associated with several mechanisms including interference of vital signaling pathways targeted by the antibody and immune cytotoxicity selectively directed against tumor cells by tumor-bound antibody through the Fc portion of the antibody, such as antibody-dependent cellular cytotoxicity and complement-dependent cytotoxicity. Moreover, recent experimental findings have shown that immune complexes formed by therapeutic mAbs with tumor-released antigens could augment the induction of tumor-specific cytotoxic CD8 + T cells through activation of APCs. In addition, antibodies targeting immune checkpoints on hematopoietic cells have recently opened a new avenue for the treatment of cancer. In this review, we focus on mAb treatment in colorectal cancer and its immunological aspects.